Biodegradable Cup as A Substitute for Single Use Plastic - Sazeli, Zul Afiq; Zailani, Arash; Tajudin, Irfan; Alif, Hamka (Multidisciplinary Applied Research and Innovation, 2021)
Be it on thin ice, plastic waste is not easily recycled or composed because it is not an organic material, and a large amount of plastic waste has been improperly disposed due to the unregulated processing of plastic products, which has caused pollution around the world and has also shown that it is lethal to the ecosystem. The project investigates the feasibility of the biodegradable cutlery as an alternative to single-use plastics which would also serve as an important practical step in the direction of zero plastic use and waste along with the limitations. It be made from organic material like corn and barley and is an ideal alternative to any plastic tableware and cutlery. Grinding, mixing, heating, compressing, cutting and no chemical compounds are required for the process. By looking at the quality of product, they can replace the plastic cutlery as the quality of biodegradable cutlery from organic materials are near to the perfect characteristic of the plastic one. All the tests that are conducted would be determined the overall result that brings toward the idea of eliminating the single-use plastic that helps to have a healthier, safer and greener future.